Kartellrechtliche Anforderungen an private Rechtssysteme im Sport - Putzier, Konstantin Richard (Beiträge zum Sportrecht, 2021)
»Competition Law Requirements on Private Legal Systems in Sport«: The pyramidal system of associations, the special characteristics of sports competition and the conflict between competition law and the fundamental right of freedom of association lead to challenges in the application of competition law to sports matters. This work presents the rich antitrust casuistry of the authorities and courts of the European Union and its Member States in the field of sports. It also suggests ways to resolve issues that have not yet been decided.